PERAN KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH KOMITMEN ORGANISASIONAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri Di Kecamatan Pati Kabupaten Pati) - Ambar Herumindah, 12.52.02.0222; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the influence of organizational commitment and emotional intteligence to the teacherâs performence of Public Senior High School with moderation of transformasional leadership. The specific study of this study is to examine the role of transformasional leadership moderates the influence of organizational commitment and emotional intteligence to the teacherâs performance. The usefulness of this study is toÂ explain andÂ extebnd previous study on the role of transformasional leadership moderate the influence of organizational commitment and emotional intteligence to the teacherâs performance.This study used a population of high school teachers in Pati district, Pati regency were 116 teachers. Sampling techniques in this study is non-probability sampling with purposive sampling method. The analysis technique used is the regression model of quasi moderation. Based on the resultÂ the writer can summarize as follows:The organizational commitment influents the teacherâs performance positively, the emotional inteligence influents the teacherâs performanec positively, the transformational leadership also influents the teacherâs performance positively, the transformational leadership does not moderate the influence ofÂ organizazional commitment to the teacherâs performance, the transformational leadership strengthen the influenceÂ of emotional inteligence to the teacherâs performance.Keywords: Organizational Commitment, Emotional Inttelligence, Transformational Leadership and Teacherâs Performance